Granulomatosis polyangiitis associated with meningeal involvement: response to rituximab therapy after failure of cyclophosphamide - M. Benucci; F. Li Gobbi; P. Panconesi; M. Manfredi; P. Sarzi-Puttini; F. Atzeni (PAGEPress Publications, 2013)
Wegener's granulomatosis or granulomatosis polyangiitis associated (GPA) is a granulomatous inflammation of the upper and lower respiratory tracts associated with necrotising vasculitis of small and medium-sized blood vessels and, frequently, necrotising glomerulonephritis. We describe the case of a 37 year old female patient presenting with upper respiratory tract involvement, chronic rhinosinusitis with green secretions, and bilateral hypoacusia. Ten months later, she suffered occipital headache and two episodes of lipothymia associated with nausea, photophobia, faintness with visual blurring. Magnetic resonance imaging (MRI) revealed aseptic meningitis. The patient was treated with steroids and cyclophosphamide without any effect on the neurological symptoms which, however, greatly improved after subsequent treatment with rituximab as confirmed by means of cerebral MRI. Rituximab is an optimal means of treating cyclophosphamide-resistant patients with GPA associated with meningeal involvement.